2022
DOI: 10.1162/netn_a_00258
|View full text |Cite
|
Sign up to set email alerts
|

Applying multilayer analysis to morphological, structural, and functional brain networks to identify relevant dysfunction patterns

Abstract: In recent years, research on network analysis applied to MRI data has advanced significantly. However, the majority of the studies are limited to single networks obtained from resting-state fMRI, diffusion MRI, or grey matter probability maps derived from T1 images. Although a limited number of previous studies have combined two of these networks, none have introduced a framework to combine morphological, structural and functional brain connectivity networks. The aim of this study was to combine the morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…investigated in (Battiston et al, 2017(Battiston et al, , 2018Lim et al, 2019) for one fMRIbased and an additional structural network layer for healthy controls. Recently, a framework for including -next to structural and functional layers -also a third morphological grey matter network layer has been proposed (Casas-Roma et al, 2022). Therefore, the multilayer network approach allows us to study in an individual how brain processes at different scales, from functional to structural, undergo plasticity related changes.…”
Section: Discussionmentioning
confidence: 99%
“…investigated in (Battiston et al, 2017(Battiston et al, , 2018Lim et al, 2019) for one fMRIbased and an additional structural network layer for healthy controls. Recently, a framework for including -next to structural and functional layers -also a third morphological grey matter network layer has been proposed (Casas-Roma et al, 2022). Therefore, the multilayer network approach allows us to study in an individual how brain processes at different scales, from functional to structural, undergo plasticity related changes.…”
Section: Discussionmentioning
confidence: 99%
“…The multilayer clustering coefficient quantifies the average clustering coefficient of a node across all layers, accounting for both intralayer and interlayer clustering (Buldu & Papo, 2018;Casas-Roma et al, 2022;De Domenico, 2018;Lv et al, 2021;Puxeddu et al, 2021;Shahabi et al, 2023). The mean clustering coefficient indicates how wellneighboring nodes are connected, which is related to the segregation of the network.…”
Section: Discussionmentioning
confidence: 99%
“…As the information conveyed by connectivity data is multivariate in nature and multimodal datasets become increasingly available, it has been advocated that multilayer networks, rather than single-layer architectures, may represent the ideal mathematical framework to study the brain as a complex system. [10][11][12] However, how to meaningfully model together structural and functional aspects of brain connectivity is still debated, with novel possible methodological solutions continuing to emerge. [10][11][12] The method adopted here to detect the core-periphery of multiplex networks has the advantage of minimizing the need for a priori assumptions, reducing the variable degree of arbitrariness and information loss that are inevitably associated with the processes of, e.g., thresholding/binarizing connectivity matrices or assigning predefined weights to the different layers.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] However, how to meaningfully model together structural and functional aspects of brain connectivity is still debated, with novel possible methodological solutions continuing to emerge. [10][11][12] The method adopted here to detect the core-periphery of multiplex networks has the advantage of minimizing the need for a priori assumptions, reducing the variable degree of arbitrariness and information loss that are inevitably associated with the processes of, e.g., thresholding/binarizing connectivity matrices or assigning predefined weights to the different layers. 12 In our large multi-centre population, the data-driven optimization procedure showed that all three modalities are necessary to maximize the separation between PwMS and HC in regional coreness, with greater estimated contribution coefficients for structural rather than functional layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation